The bi‐directional association between loneliness and depression among older adults from before to during the COVID‐19 pandemic. (3rd December 2022) - Ward, Mark; Briggs, Robert; McGarrigle, Christine A.; De Looze, Celine; O'Halloran, Aisling M.; Kenny, Rose Anne
Abstract: Background: Older adults have both the highest risk of contracting SARS‐CoV‐2 and in many jurisdictions have had additional restrictions placed on the social interactions. As a result, the COVID‐19 pandemic has led to increased depression and loneliness among older adults. Using data from an established cohort of older adults, the aims of this study was to describe changes in loneliness and depression and to examine the directionality of the association between depression and loneliness over a 5‐year period that included the early months of the pandemic. Methods: Data were from The Irish Longitudinal Study on Ageing (TILDA), a large cohort of community‐dwelling adults aged 54+. We applied an auto‐regressive cross‐lagged panel modelling approach to estimate the effect of depression on loneliness and vice versa over three time points. Results: Both depression and loneliness increased significantly in the early months of the pandemic. While the association between loneliness and depression was bi‐directional, loneliness was a stronger predictor of depression. Conclusion: The strength and bi‐directionality of the association between loneliness and depression suggests that interventions to alleviate loneliness may also help reduce depressive symptoms and vice versa. Key points: Loneliness and depressive symptomology among older adults increased during the COVID‐19 pandemic. The association between loneliness and depression was bi‐directional. Interventions to alleviate loneliness or depression may also reduce the other.